Ambient Air Quality Monitoring in Metropolitan City of Lagos, Nigeria - Kelechi Longinus Njoku; Tosin John Rumide; Modupe Olatunde Akinola; Adeola Alex Adesuyi; Anuoluwapo Omosileola Jolaoso (Journal of Applied Sciences and Environmental Management)
Twenty one sampling locations were assessed for carbon monoxide (CO), carbondioxide (CO2), oxygen (O2), sulphur dioxide (SO2), nitrogen dioxide (NO2), nitrogen oxide (NO), suspended particulate matter (SPM) and noise level using air pollutants measurement methods approved by ASTM for each specific parameter. All equipments and meters were all properly pre-calibrated before each usage for quality assurance. Findings of the study showed that measured levels of noise (61.4 - 101.4 dBA), NO (0.0 - 3.0 ppm), NO2 (0.0 - 3.0 ppm), CO (1.0 – 42.0 ppm) and SPM (0.14 – 4.82 ppm) in all sampling areas were quite high and above regulatory limits however there was no significant difference except in SPM (at all the sampling points), and noise, NO2 and NO (only in major traffic intersection). Air quality index (AQI) indicates that the ambient air can be described as poor for SPM, varied from good to very poor for CO, while NO and NO2 are very good except at major traffic intersection where they were both poor and very poor (D-E). The results suggest that strict and appropriate vehicle emission management, industrial air pollution control coupled with close burning management of wastes should be considered in the study area to reduce the risks associated with these pollutants.© JASEM